A fast microwave-assisted, acid-vapor, steam-cleaning procedure for autosampler cups - Barnes, Ramon M.; Quinaia, Sueli P.; Nóbrega, Joaquim A.; Blanco, Thelma [UNESP] (Elsevier B.V., 1998)
A new and fast procedure is proposed for cleaning autosampler cups using acid-vapor steam-cleaning with a miniaturized assembly in a microwave-heated sealed Teflon vessel. A glass cactus-shaped holder was made to support six polyethylene autosampler cups (volume, 2.0 mt) inside a 100 mt microwave vessel. Regent-grade nitric acid was added to the vessels, and the system was heated in a microwave oven for 5 min at 300 W. Chromium was determined by graphite-furnace atomic-absorption spectrophotometry. The blank values were lower with cleaned cups compared to untreated cups (i.e., as received from supplier). The quantification limits, estimated from detection limits established with Milli-Q water, were 0.66 and 0.95 mu g Cr L-1 for cleaned and untreated auto-sampler cups, respectively. (C) 1998 Elsevier B.V. B.V. All rights reserved.
Keywords: vapor-phase cleaning; autosampler cups; Cr; graphite-furnace atomic-absorption spectrophotometry